Dialogue between the State and Religion as a Basis for Managerial Decision-Making: Research Experience in the Regions of the North-West - Ju. P. Bayer; V. D. Kovalenko; E. V. Rodionova; N. K. Syundyukov (Управленческое консультирование)
The article is based on the results of a large research project “State and Religion in the North-West: a sociological analysis”, which was conducted by the RANEPA in 2020, and was aimed at developing and implementing an interdisciplinary methodology for analyzing the religious situation in the Northwest Federal District. The article presents the results of a study of the relationship between the state and religious institutions in 5 regions of the Federal District. The article presents theoretical developments in the perspective of modern state-confessional relations, the study of the mediatization of religion, concludes about the multi-tiered structure of modern communication between the state and religious organizations on the Internet, as well as about the significance of the symbol and religious holiday in the public public sphere. The methods of empirical research were content analysis and expert interviews with an emphasis on both different regions and a combination of factors throughout the North-Western Federal District as a whole. The results of the study show that there is a strong interrelationship between social and religious processes in the subjects of the federation. But there are some regional differences, first of all in the role of media in different regions.